INDUSTRIAL HEMP VARIETIES PRODUCTIVITY POTENTIAL IN THE LATVIAN CLIMATIC CONDITIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Varieties grown for fibre-only will be established, managed and harvested differently than varieties grown for seeds or dual-purpose. The aim was analysed yield productivity and length of vegetation period dependency of the two types of hemp variety and identified perspective hemp variety for highest yield under different meteorological conditions in Latvia. Varieties/line from diverse European and Latvian origin (seed hemp varieties/ line 'Adzelvieši', 'Pūriņi', KA-2-2011, 'Finola', 'Henola' and fibre hemp varieties 'USO 31', 'Futura 75', 'Austa') were sown in randomized field experiments in Latvia. Biomass, stem, seed yield, fibre contents and vegetation period length were assessed across tree growing seasons from 2020 to 2022. Results show that hemp, seeds and fibre varieties/line, performed well giving high yield productivity between variety. Agrometeorological conditions for hemp growth and yield were favourable in 2022. In Latvian local climatic conditions, the seed hemp line KA-2-2011 and fibre hemp variety ‘Futura 75’ identified significant higher of biomass and stem yield as well as the seed hemp variety ‘Henola’ and fibre hemp variety ‘Austa’ significant higher of seed yield and fibre contents. The yield potential dependent from length of vegetation period length. The trial analyses identified positive and significant correlations between length of vegetation period and biomass (r = 0.97), stem yield (r = 0.98), and negative between length of vegetation period and seed yield (r = -0.89).